Decreased apoptosis despite severe CD4 depletion in the thymus of a human immunodeficiency virus-1 infected child = Verminderte Apoptose trotz ausgepräägter CD4-Depletierung im Thymus bei einem an Immundefizienz durch Human Immunodeficiency Virus-1 (HIV1) erkrankten Kind - Brunner, Jürgen; Boehler, T.; Ehemann, Volker; Kassam, S.; Otto, H.; Sergi, C. (Klinische Pädiatrie, 2011)
Thymic epithelial space (TES), where thymopoiesis is located, and thymic perivascular space (PVS), where T lymphocytes are pooled, appear differentially involved in human immunodeficiency virus 1 (HIV-1)-infected children. The decline of CD4 + T cells during HIV-1 infection is probably due to a relative predominance of CD4 + T cell destruction on cell proliferation. Antiretroviral therapy (ART) typically increases circulatÂing CD4 + T cell counts, but it is debated whether ART reduces the destruction of existing CD4 + T cells or enhances the production of new cells. We report on postmortem flow-cytometry, immunohistochemistry, and terminal deoxynucleotide transferase (TdT)-mediated dUTP nick-end labeling (TUNEL) studies performed on thymus of an 11-year-old vertically HIV-1 infected child receiving ART. Thymus tissue sections showed that CD4 + and CD8 + cells were more numerous in PVS than in TES (p = 0.0334 for CD4 + cells, p < 0.0001 for CD8 + cells). Thymus cell suspension showed that CD4 + CD8 + cells (immature thymocytes) were 15.4% (age-related control: 80.5 %). Very few apoptotic CD4 + cells were seen in TES. Very low to absent proliferation activity was demonstrated in both TES and PVS. We suggest that 1) lymphocyte depletion in HIV-1 infection is more pronounced in TES than in PVS, 2) immature thymocytes are not enhanced, and 3) an anti-apoptotic effect in the thymus seems to be a potential ART mechanism to explain the CD4+ pool increase.
Gesehen am 24.06.2022